Determining Fish Assemblage Structure Using Elevation in the Swannanoa River - Wynn Arellano (UNC Test Journal, 2024)
The effects of urbanization and climate change have altered fish assemblages in streams. These effects will allow some fish species to colonize new habitats, have their resource and habitat niches reduced, or retreat upstream to escape into tributaries. The goal of this study was to see what species are affected by these changes in the Swannanoa River and its tributaries by looking at fish assemblage across an elevation gradient. Six sites were sampled in the mainstem Swannanoa and eight in the tributaries. I conducted tests to get species correlation across elevation, along with the Shannon diversity index and species abundance for each site. A low-head dam appeared to affect assemblage with several species present only above or below the dam. Sites below the dam were urban while sites above were relatively forested. These urban sites had low numbers of Central Stonerollers, suggesting that below the dam does not support the species well. This was unexpected as urban streams tend to have more algae, a food source for the species. The Shannon diversity index and species abundance found above the dam reflect what would be expected at the lower sites. Cold-water species such as Mottled Sculpin, Rainbow and Brown Trout were positively correlated with elevation. These results contradict previous studies that found more species downstream compared to upstream. My results suggest that urbanization contributes to the poor conditions in the lower sites, while the dam acts as a boundary between stream conditions. To get better conditions in the stream and reduce the effects of urbanization, stream restoration efforts could be done.